Isolation, characterization, and genome sequencing of a novel chitin deacetylase producing Bacillus aryabhattai TCI-16 - Liang, Ying-yin; Yan, Lu-qi; Tan, Ming-hui; Li, Gang-hui; Fang, Jian-hao; Peng, Jie-ying; Li, Kun-tai (Frontiers in Microbiology, 2022)
Chitin deacetylase (CDA) is a chitin degradation enzyme that catalyzes the conversion of chitin to chitosan by the deacetylation of N-acetyl-D-glucosamine residues, playing an important role in the high-value utilization of waste chitin. The shells of shrimp and crab are rich in chitin, and mangroves are usually recognized as an active habitat to shrimp and crab. In the present study, a CDA-producing bacterium, strain TCI-16, was isolated and screened from the mangrove soil. Strain TCI-16 was identified and named as Bacillus aryabhattai TCI-16, and the maximum CDA activity in fermentation broth reached 120.35±2.40 U/mL at 36 h of cultivation. Furthermore, the complete genome analysis of B. aryabhattai TCI-16 revealed the chitin-degrading enzyme system at genetic level, in which a total of 13 putative genes were associated with carbohydrate esterase 4 (CE4) family enzymes, including one gene coding CDA, one gene encoding N-acetylglucosamine deacetylases, and 5 genes encoding peptidoglycan-N-acetyl glucosamine deacetylases. Amino acid sequence analysis showed that the predicted CDA of B. aryabhattai TCI-16 was composed of 236 amino acid residues with a molecular weight of 27.3 kDa, which possessed a conserved CDA active like the known CDAs. However, the CDA of B. aryabhattai TCI-16 showed low homology (approximately 30%) with other microbial CDAs, and its phylogenetic tree belonged to a separate clade in bacteria, suggesting a high probability in structural novelty. In conclusion, the present study indicated that the novel CDA produced by B. aryabhattai TCI-16 might be a promising option for bioconversion of chitin to the value-added chitosan.